First paleo-environmental considerations on the pleistocene depositsof the Lower Cave of Covoli di Velo (VR - Italy) - F. Bona; R. Zorzin; M. Accordini; R. Mazzi; C. A. Accorsi; M. Bandini Mazzanti; G. Bosi; G. Trevisan; P. Torri; GATTO, ROBERTO (2006)
From 2001 until today over 2.000 remains of Ursus spelaeus, cave bear of this karstic system, have emerged from the five year excavation in the Lower Cave of Covoli di Velo. Therefore this cavity has returned a real paleonthological patrimony, on which important studies have already been performed in order to get data on the population of cave bears of this karstic system. Unfortunately, during this five year research we did not have similar luck with other species, despite evidence by various authors of the presence of a rich fauna of vertebrates in these caves in the past. In fact, few finds have been retrieved, revealing only three macro-mammal species: Canis lupus, Crocuta crocuta spelaea and Capra ibex. Therefore, in these last campaigns we decided to sample different sectors and levels of excavation B, in order to get information about the micro-mammals of these Pleistocene deposits. However, the amount of determinable material, retrieved by sifting sediment, is very scarce. It was, in fact, only a few teeth and jaws that led us to identify the following species: Glis glis, Microtus arvalis, Microtus agrestis, Microtus oeconomus, Chionomys nivalis, Dinaromys bogdanovi, Terricola sp. (Rodentia), Sorex minutus (Insectivora), Myotis blythi, Myotis sp., Miniopterus schreibersi, Rhinolophus sp. (Chiroptera). We then tried to cross examine these results with those of the pollen analysis of three samples taken from different depths of sector B. The results obtained from the pollen, combined with those of the fauna, give us interesting matters of discussion and further ideas on the possible paleo-environment of Covoli di Velo during Late Pleistocene.